Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Wolstenholme Theorem is a nice theorem that states that every prime $p >3$ satisfies:

$$\binom{2p}{p} \equiv 2 \pmod {p^3}$$

A Wolstenholme prime is a prime $p$ such that $\binom{2p}{p} \equiv 2 \pmod {p^4}$. There are several equivalent criteria for this. I was able to prove myself or find proofs on the internet that any of following congruences is equivalent to $p$ being a Wolstenholme prime: $$\sum_{i=1}^{p-1} i^{-2} \equiv 0 \pmod {p^2}$$ $$\sum_{1 \le i < j \le p-1} \frac{1}{ij} \equiv 0 \pmod {p^2}$$ $$p\sum_{1 \le i < j \le p-1} \frac{1}{ij} + \sum_{i=1}^{p-1} \frac{1}{i} \equiv 0 \pmod {p^3}$$

The proofs are expanding $\binom{2p}{p} = 2\frac{\prod_{i=1}^{p-1} (i+p)}{\prod_{i=1}^{p-1} i}$ in different ways. But in Wikipedia I found the nicest criterion:

$$\sum_{i=1}^{p-1} \frac{1}{i} \equiv 0 \pmod {p^3}$$

This congruence is implies by the last 2 criteria, but I am not sure how it implies one of the criteria. Is there an elementary proof of this?

share|cite|improve this question
up vote 2 down vote accepted

OK, I eventually solved it myself. The manipulation is the following:

$$ \sum_{i=1}^{p-1} \frac{1}{i} = \frac{1}{2} (\sum_{i=1}^{p-1} \frac{1}{i} + \frac{1}{p-i}) = \frac{-p}{2} (\sum_{i=1}^{p-1} \frac{1}{i(i-p)}) $$ $$ = \frac{-p}{2} (\sum_{i=1}^{p-1} \frac{1}{i^2} +\frac{1}{i(i-p)} - \frac{1}{i^2})$$ $$ = \frac{-p}{2} (\sum_{i=1}^{p-1} \frac{1}{i^2} +\frac{1}{i}(\frac{1}{i-p}-\frac{1}{i}))$$ $$ = \frac{-p}{2} (\sum_{i=1}^{p-1} \frac{1}{i^2} +\frac{p}{i}\frac{1}{i(i-p)})$$ $$ = \frac{-p}{2} (\sum_{i=1}^{p-1} \frac{1}{i^2} + p\frac{1}{i^2(i-p)})$$

Since $p | \sum_{i=1}^{p-1} \frac{1}{i^3}$ for $p>3$, we have $p | \sum_{i=1}^{p-1} \frac{1}{i^2(i-p)}$ for $p>3$ which implies: $ p^3 | \sum_{i=1}^{p-1} \frac{1}{i}$ iff $p^2 | \sum_{i=1}^{p-1} \frac{1}{i^2}$.

This shows that the very first criterion, $p^2 | \sum_{i=1}^{p-1} \frac{1}{i^2}$ (which follows from the proof to Theorem 1 in this paper, see page 3) is equivalent to the nice criterion $H_{p-1}$ being divisible by $p^3$ (at least for $p>3$. $p=2,3$ can be verified seperately).

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.